Kontribusi Motivasi dan Prestasi Belajar terhadap Kemampuan Mengajar Mahasiswa - B. Sukarno (Universitas Negeri Malang, 2016)
The purpose of this research is to describe the contribution of students' motivation and learning achievement to their teaching capabilities. The sample consisted of 56 selected randomly from 60 students of the Department of Accountancy Education, UNS Surakarta. A questionnaire and documentary study were used to collect data. The data were analysed by multiple regression. The results indicated that the contribution of students' motivation and learning achievement in the basic-general courses (MKDU), basic-educational courses (MKDK), learning-teaching process courses (MKPBM), and subject-matter courses (MKBS) to their teaching capabilities was significant